BCG Vaccination Prevents Reactivation of Latent Lymphatic Murine Tuberculosis Independently of CD4+ T Cells - Sathkumara, Harindra D.; Pai, Saparna; Aceves-Sánchez, Michel de Jesús; Ketheesan, Natkunam; Flores-Valdez, Mario Alberto; Kupz, Andreas (Frontiers in Immunology, 2019)
Tuberculosis (TB) is a major global public health problem causing significant mortality and morbidity. In addition to approximately 10.4 million cases of active TB annually, it is estimated that about two billion people are latently infected with Mycobacterium tuberculosis (Mtb), the causative agent of TB. Reactivation of latent Mtb infection is the leading cause of death in patients with immunodeficiency virus (HIV) infection. The low efficiency of the only licensed anti-TB vaccine, Bacille Calmette–Guérin (BCG) to reduce pulomonary TB in adults contributes to this problem. Here we investigated if vaccination with conventional BCG or the genetically modified experimental BCGΔBCG1419c strain can prevent reactivation of latent lymphatic TB in a mouse model of induced reactivation, following the depletion of CD4+ T cells, as it occurs in HIV+ individuals. Vaccination with conventional BCG and BCGΔBCG1419c prevented reactivation of Mtb from the infected lymph node and the systemic spread of Mtb to spleen and lung. Prevention of reactivation was independent of vaccination route and was accompanied by reduced levels of circulating inflammatory cytokines and the absence of lung pathology. Our results demonstrate that vaccine-induced CD4+ T cells are not essential to prevent reactivation of latent lymphatic murine TB, and highlight the need to better understand how non-CD4+ immune cell populations participate in protective immune responses to control latent TB.